KERAMBA IKAN SEBAGAI ALTERNATIF PEMELIHARAAN KEBERSIHAN SUNGAI DARI KEBIASAAN BUANG AIR BESAR DAN SAMPAH DI DESA BENELANLOR KECAMATAN KABAT - Ellyana Ilsan Eka Putri; Mufidah Yusroh (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2020)
A river is one of natural resources which used by village people to fulfil daily needs. Those daily lives are such as taking a bath, washing clothes even for toileting. Some of them also use it as dusbin. This is actually having negative effects for their health themselves. Implementing fish farming along the river by Islamic Institute Ibrahimy Genteng dedication tim through KKN and it cooperated with Karang Taruna and Benelan Lor people in order to minimize the usage of river by people surrounding as their daily needs that will cause their health and it will potentially bother the other ecosytems.